Eating in the Absence of Hunger and Weight Gain in Low-income Toddlers - Asta, Katharine (Pediatrics, 2016)
OBJECTIVE: To identify predictors of eating in the absence of hunger (EAH) in low-income toddlers, describe affect during EAH, test EAH as a predictor of body mass index (BMI), and examine the type of food eaten as a predictor of BMI. METHODS: EAH, indexed as kilocalories (sweet, salty, and total) of palatable foods consumed after a satiating meal, was measured (n = 209) at ages 21, 27, and 33 months. Child gender, age, race/ethnicity, and previous exposure to the foods; maternal education and depressive symptoms; and family chaos, food insecurity, and structure were obtained via questionnaire. Child and mother BMI were measured. Child affect was coded from videotape. Linear regression was used to examine predictors of EAH and the association of kilocalories consumed and affect with 33 month BMI z-score (BMIz). RESULTS: Predictors of greater total kilocalories included the child being a boy (P < .01), being older (P < .001), and greater maternal education (P < .01). Being in the the top quartile of sweet kilocalories consumed at 27 months and showing negative affect at food removal had higher BMIz (β = 0.29 [95% confidence interval 0.10 to 0.48] and β = 0.34 [95% confidence interval, 0.12 to 0.56], respectively).There was no association of salty kilocalories consumed or positive affect with BMIz. CONCLUSIONS: There was little evidence that maternal or family characteristics contribute to EAH. EAH for sweet food predicts higher BMIz in toddlerhood. Studies investigating the etiology of EAH and interventions to reduce EAH in early childhood are needed.